Traditional Market Development Planning in Improving the Existence of Traditional Market (A Case Study of a Traditional Market in Tulungagung Regency) - Rendi Wicaksono (Jurnal Administrasi Publik, 2017)
The plan to establish a traditional market in Tulungagung Regency done with a purpose to maintain the existence of traditional markets as well as to enhance the economy. The finding shows that the focus of the traditional market development in Tulungagung regency is only on the physical aspects, aspects are being ignored, namely the human (seller) resources, zonation, sanitation, and accessibility. Government, non-governmental organizations, and local people were all involved in making the plan. However, in designing the traditional market development plan, the local people were not given enough space to give their aspirations. Some other contributing factors are the policy of prioritizing the development, the reinforcement of budget, and the condition of the locals of Tulungagung regency. Meanwhile, some obstacles are the low quality of the sellers, just focus on infrastructure development, inconsistency of implementation zoning policy between modern and traditional market, and the loss of the rental rights and the high rental prices for new stores.